Protective solution during extraction of propane-butane - Ясиніцький, Е.П.; Лигін, В.О.; Ярмілко, Р.Ю. (Proceedings of National Aviation University (archive), 2009)
Was offered a complex of measures to rise up the safety of work technological equipment by receiving propane-butane on entrails of natural gas in condition of compressornal station.